Implementasi Tahap Produksi pada Pengembangan Game Edukasi Tingkuluak Berbasis Unity Menggunakan Teknik Scripting - Arfan Maulana; Nusrito Zalins Adekory (Al-DYAS, 2026)
Although the development of culture-based educational games offers opportunities for preserving local heritage, studies on the implementation of scripting techniques during the production stage remain limited. This study aimed to describe the implementation of the production stage in the development of the Unity-based Tingkuluak educational game. The study employed a research and development approach with a Game Development Life Cycle design comprising the initiation, preproduction, production, testing, and release stages. Data were collected through an interview with a cultural expert, an initial questionnaire administered to 101 respondents, documentation, a literature review, alpha testing by an expert, and beta testing involving five users aged 11–18 years. The data were analyzed using qualitative and quantitative descriptive methods. The results showed that scripting techniques successfully integrated character movement, dialogue, object interactions, scene transitions, minigames, and the Album Budaya into a unified gameplay system. The beta testing results yielded an average score of 4.63 on a 5-point scale, while the feasibility aspect as a cultural education medium received a score of 5.00. Character animation received the lowest score of 4.20 and therefore still requires improvement. This study strengthens the application of the Game Development Life Cycle and scripting techniques in the development of culture-based educational media and produces a production workflow that can be used to integrate various game features. Further development should involve a broader range of respondents, improve character animation, and assess improvements in users’ knowledge through pretests and posttests.